Intravenous hydration according to current guidelines in the prevention of contrast induced nephropathy—the AMACING trial - Nijssen, Estelle C.; Nelemans, Patty J.; Rennenberg, Roger J.; Essers, Brigitte A.; Janssen, Marga M.; Vermeeren, Marja A.; van Ommen, Vincent; Wildberger, Joachim E. (Journal of Thoracic Disease; Vol 9, No 7 (July 31, 2017): Journal of Thoracic Disease, 2017)
We thank Vikram Raje and Akira Sato and colleagues for their interest in our work. To put the AMACING trial into perspective, the guideline on contrast induced nephropathy (CIN) is one of ten measures to increase patient safety in the Netherlands. Since their introduction and to date, the ten measures have been imposed on hospitals quite strictly, and compliance to these is part of the annual hospital quality assessment carried out by government instances. However, the intravenous hydration to prevent CIN was introduced without its effect having been proven, and its implementation incurs risk of clinical complications as well as increased health care costs.